Time Norms in the Workplace: Their Exclusionary Effect and Potential for Change - Smith, Belinda M. (Columbia Journal of Gender and Law, 2002)
Americans who wish to participate in paid work and have a family are confronted with many different barriers to a satisfactory combination of the two. One significant barrier is the prevalence of full-time positions as the dominant form of employment. This article explores the role played by law in perpetuating exclusionary working time norms and the way it also offers some scope for challenging them. The lack of legitimate part-time jobs limits the options that people have to successfully combine the demands of employment and family. Family responsibilities impose time demands. The long hours of full-time employment positions, and the inflexible schedules that often go with those hours expectations, are not clearly compatible with these family demands. Part-time jobs are generally less available and less legitimate in that they are usually paid at a lower rate than their full-time counterparts, do not offer comparable or even proportional benefits, and amount to contingent employment or the career mommy-track.